Math, asked by Manya21120, 7 months ago

Multiply -3xy × ( 7x^2 - 5 xy + 8 y^2 + 9)​

Answers

Answered by vrkinage68
0

Answer:

Step-by-step explanation:

(i)

 5x + 7x + (-6x)

= 5x + 7x -6x

= 6x

(ii)

35x +23x +−45x=9x +10x −12x15=7x15

(iii)  

5a2b +( −8a2b)  + 7a2b

= 5a2b − 8a2b + 7a2b

4a2b

(iv)

 34x2 + 5x2+ (−3x2 ) + (−14x2)=34x2 − 14x2 + 5x2−3x2=12x2 + 2x2 = 52x2

(v) Collecting like terms and adding them:

x − 3y + 4z + y − 2x − 8z + 5x − 2y − 3z

= x- 2x + 5x - 3y + y - 2y + 4z - 8z - 3z        

= 4x -4y -7z

(vi) Collecting like terms and adding them:

2x2 − 3y2 + 5x2 + 6y2 + (− 3x2 − 4y2)

= 2x2 + 5x2 − 3x2 − 3y2 +6y2 −4y2= 4x2 −y2                    

(vii) Collecting like terms and adding them:

5x − 2x2 − 8 +  8x2 − 7x − 9 +  3 + 7x2 − 2x

= −2x2 +8x2 + 7x2 + 5x − 7x − 2x −8 −9 + 3= 13x2 −4x −14      

(viii) Collecting like terms and adding them:

Similar questions